2005
DOI: 10.1007/s10734-004-6358-9
|View full text |Cite
|
Sign up to set email alerts
|

Through the magnifying glass: A descriptive theoretical analysis of the possible impact of the South African higher education policies on academic staff and their job satisfaction

Abstract: This article provides a descriptive theoretical analysis of the most important higher education policies and initiatives which were developed by the democratically elected government of South Africa after 1994 to transform the South African higher education system. The article sheds light on the rationale for the policies under scrutiny; how they take cognisance of academics' diverse needs; as well as how their implementation is bound to affect academics and possibly influence job satisfaction. The article arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
0
12
0
1
Order By: Relevance
“…To support this observation, Kipkebut (2010) argued that promotion for lecturers is dependent on teaching, research and publications but due to financial constraints, non-prioritisation of research by government and inadequate publishing facilities, publishing of refereed articles has become a monumental challenge in Kenya and among other African academics. Further, already concerns about academics not having sufficient time to publish and engage in research activities, aspects which are crucial for promotion and for building stature as an academic, loom in academic debates (Mapesela & Hay, 2005). …”
Section: Figure 1: Distribution Of Lecturers and Deans By Designationmentioning
confidence: 99%
“…To support this observation, Kipkebut (2010) argued that promotion for lecturers is dependent on teaching, research and publications but due to financial constraints, non-prioritisation of research by government and inadequate publishing facilities, publishing of refereed articles has become a monumental challenge in Kenya and among other African academics. Further, already concerns about academics not having sufficient time to publish and engage in research activities, aspects which are crucial for promotion and for building stature as an academic, loom in academic debates (Mapesela & Hay, 2005). …”
Section: Figure 1: Distribution Of Lecturers and Deans By Designationmentioning
confidence: 99%
“…The impact of Higher Education Commission of Pakistan policies on academic staff and their satisfaction was found inconsistent (Mapesela & Hay, 2005). They found that most of the policies have negative correlation with academic staff performance and their job satisfaction.…”
Section: Hrm Practices and Job Satisfactionmentioning
confidence: 99%
“…Quality Agencies have produced generally acceptable norms of conduct usually expected of HEIs. The values, mission and aims of the institution should first be identified and established before an academic quality model can be developed (Mapesela & Hay, 2005). Social demand for HE has been on the increase over the past few decades.…”
Section: Diagram 11: the Planning Processmentioning
confidence: 99%